Core outcome set for surgical trials in gastric cancer (GASTROS study): international patient and healthcare professional consensus. Issue 10 (24th June 2021) - Alkhaffaf, B; Metryka, A; Blazeby, J M; Glenny, A -M; Adeyeye, A; Costa, P M; Diez del Val, I; Gisbertz, S S; Guner, A; Law, S; Lee, H -J; Li, Z; et al.
Abstract: Background: Surgery is the primary treatment that can offer potential cure for gastric cancer, but is associated with significant risks. Identifying optimal surgical approaches should be based on comparing outcomes from well designed trials. Currently, trials report different outcomes, making synthesis of evidence difficult. To address this, the aim of this study was to develop a core outcome set (COS)—a standardized group of outcomes important to key international stakeholders—that should be reported by future trials in this field. Methods: Stage 1 of the study involved identifying potentially important outcomes from previous trials and a series of patient interviews. Stage 2 involved patients and healthcare professionals prioritizing outcomes using a multilanguage international Delphi survey that informed an international consensus meeting at which the COS was finalized. Results: Some 498 outcomes were identified from previously reported trials and patient interviews, and rationalized into 56 items presented in the Delphi survey. A total of 952 patients, surgeons, and nurses enrolled in round 1 of the survey, and 662 (70 per cent) completed round 2. Following the consensus meeting, eight outcomes were included in the COS: disease-free survival, disease-specific survival, surgery-related death, recurrence, completeness of tumour removal, overall quality of life, nutritional effects, and 'serious' adverse events. Conclusion: A COS for surgical trials in gastric cancer has been developed with international patients and healthcare professionals. This is a minimum set of outcomes that is recommended to be used in all future trials in this field to improve trial design and synthesis of evidence. Abstract : Outcomes in surgical trials for gastric cancer are reported heterogeneously and do not sufficiently reflect the priorities of key stakeholders, including patients. This contributes to outcome reporting bias and research waste. To address these challenges, a core outcome set—a minimum group of critically important outcomes to be reported in future trials— has been developed through an international consensus process involving patients and healthcare professionals.